Research on the Difference of Urban and Rural Home Environment from the Perspective of Family Education-Taking Basic Education as an Example - Zhang, Yintao; Chen, Xianqiang (Journal of Research in Vocational Education, 2024)
Family education is the first teacher for children to teach, is the innate environment for children to learn, is an important driving force. In the content of family education, there are many influencing factors, and the improvement of home environment has a far-reaching impact on children's education significance. The subtle "infectious" education from families is deeply rooted, especially in childhood. Studies have shown that children at the age of 6-12 will determine their life ideals according to the family education environment, parents' words and deeds, and strive for them all their life, and it is not easy to be changed in adulthood. This paper compares the differences between urban and rural home environment in Luojiang area, especially the similarities and differences in the living environment of urban and rural primary and secondary schools, to create a learning environment suitable for children's physical and mental development and can assist parent-child family education; and provides solutions to improve the poor learning efficiency and the phenomenon of students' passive interest in learning. By virtue of the emotional regulation advantages of the community and the family living environment, the synchronous development and stable improvement of urban and rural family education, so as to provide intellectual support for promoting the quality of urban and rural family education, improving the steady development of the integration of basic education in Luojiang region, and promoting the regional prosperity in Luojiang region.